2023
DOI: 10.1093/mnras/stad525
|View full text |Cite
|
Sign up to set email alerts
|

MOJAVE – XX. Persistent linear polarization structure in parsec-scale AGN jets

Abstract: We analysed the parsec-scale linear polarization properties of 436 active galactic nuclei (AGN) based on 15 GHz polarimetric Very Long Baseline Array (VLBA) observations. We present polarization and total intensity images averaged over at least five epochs since 1996 January 19 through 2019 August 4. Stacking improves the image sensitivity down to ∼30 μJy beam−1 and effectively fills out the jet cross-section both in total intensity and linear polarization. It delineates the long-term persistent magnetic field… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 98 publications
3
34
0
Order By: Relevance
“…The EVPA is almost perpendicular to the direction of the jet, suggesting that a poloidal magnetic field dominates this region. This is consistent with the statistics that the spatial distribution of EVPAs in radio galaxies shows an excessive orthogonal polarization orientation based on the linear polarization properties of 436 AGNs (Pushkarev et al 2023). However, the toroidal magnetic field with an average EVPA of −40°is comparable to the poloidal field in the knot region.…”
Section: Polarizationsupporting
confidence: 89%
“…The EVPA is almost perpendicular to the direction of the jet, suggesting that a poloidal magnetic field dominates this region. This is consistent with the statistics that the spatial distribution of EVPAs in radio galaxies shows an excessive orthogonal polarization orientation based on the linear polarization properties of 436 AGNs (Pushkarev et al 2023). However, the toroidal magnetic field with an average EVPA of −40°is comparable to the poloidal field in the knot region.…”
Section: Polarizationsupporting
confidence: 89%
“…In the jet region, Pushkarev et al (2023) also found that the EVPAs in quasars tend to be preferentially transverse to the jet in the outer ridge line regions. For the jet of 1604+159, we did not detect the EVPA transverse to the jet but had a large separation of ∼ ± 40°from the jet direction, where positive and…”
Section: Linear Polarization Distributionmentioning
confidence: 76%
“…MOJAVE monitored the source 1604+159 for six epochs from 2009 to 2013 at 15 GHz (Lister et al 2018) and studied the source with stacking (Pushkarev et al 2023). Stacking has the advantage of improving the image sensitivity and providing a complete jet cross section structure as much as possible by utilizing existing data; through distributions of EVPA and fractional polarization, stacking shows long-term persistent magnetic field configuration (Pushkarev et al 2023).…”
Section: The Magnetic Field In the Jetmentioning
confidence: 99%
See 2 more Smart Citations